‘Better off alone than in bad company’: agonistic colour display in mimetic juveniles of two ephippid species - B. Barros; Y. Sakai; H. Hashimoto; K. Gushima; M. Vallinoto (Journal of Fish Biology, 2012)
Comparative field observations of agonistic interactions in juvenile leaf‐mimicking Platax orbicularis and Chaetodipterus faber (Ephippidae) were conducted in coastal waters of the Pacific and Atlantic Oceans. Similar agonistic behaviour was observed in the two species, in which individuals stopped displaying their mimetic colouration during encounters with conspecifics, to display conspicuous colours, such as transverse stripes along the body. These events were observed occasionally, almost invariably in individuals of smaller body size. Larger‐bodied individuals of both species spent less time in agonistic displays. The absolute size of the fish, however, did not appear to affect the outcome of the encounter, suggesting that dominance is a temporary condition, based on the relative size of the opponents during encounters.